Declining Amenable Mortality: Time Trend (2000–2013) and Geographic Area Analysis - Gianino, Maria Michela (Health Serv Res, 2016)
OBJECTIVE: To update amenable mortality in 32 OECD countries at 2013 (or last available year), to describe the time trends during 2000–2013, and to evaluate the association of these trends with various geographic areas. DATA SOURCES: Secondary data from 32 countries during 2000–2013, gathered from the World Health Organization Mortality Database. STUDY DESIGN: Time trend analysis. DATA COLLECTION: Using Nolte and McKee's list, age‐standardized amenable mortality rates (SDRs) were calculated as the annual number of deaths over the population aged 0–74 years per 100,000 inhabitants. We performed a mixed‐effects polynomial regression analysis on the annual SDRs to determine whether specific geographic areas were associated with different SDR trajectories over time. PRINCIPAL FINDINGS: The OECD average annual decrease was 3.6/100,000 (p < .001), but slowed over time (coefficient for the quadratic term = 0.11, p < .001). Eastern and Atlantic European countries had the steepest decline (−6.1 and −4.7, respectively), while Latin American countries had the lowest slope (−1.7). The OECD average annual decline during the 14‐year period was −0.5 (p < .001) for cancers and −2.5 (p < .001) for cardiovascular diseases, with significant differences among countries. CONCLUSION: Declining trend of amenable SDRs was continuing to 2013 but with steepness change compared with previous periods and with a slowdown.